2017
DOI: 10.1021/acscatal.7b01374
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of How Moisture Enhances CO Oxidation over Au/BN at Ambient Temperature

Abstract: Gold catalysts readily catalyze CO oxidation at subambient temperature, wherein moisture can influence the activity, typically with a volcano-shaped dependence. In this study, we examine moisture-enhanced CO oxidation over Au/BN. The room-temperature CO oxidation activity of Au/BN increases quickly with increasing moisture content up to 100% relative humidity (RH). In situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and in situ UV–vis diffuse reflectance spectroscopy (UV-vis-DRS) demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 74 publications
4
34
0
Order By: Relevance
“…To further explore the dissociation of CH 4 , we recorded the additional in situ DRIFTS spectra of the O 2 ‐pretreated PdW 1 /Al 2 O 3 and Pd/Al 2 O 3 samples for CH 4 oxidation at different temperatures (Figure S17). With the rise in temperature in a continuous 0.5 vol % CH 4 /N 2 flow, the bands at 966, 1070–1220, and 1465 cm −1 are attributed to the vibration modes of the ν Pd(O2) of the surface peroxo species Pd(O 2 ), [14c, 19] the δ (OO−H) of PdOOH, [14] and the δ (CH) of CH 3 −O−Pd, [15b] respectively. This indicates that C−H bonds are cleaved with the reaction of the active oxygen to form the radical‐like CH 3 species and nearly form the OOH bonds in a transition state.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the dissociation of CH 4 , we recorded the additional in situ DRIFTS spectra of the O 2 ‐pretreated PdW 1 /Al 2 O 3 and Pd/Al 2 O 3 samples for CH 4 oxidation at different temperatures (Figure S17). With the rise in temperature in a continuous 0.5 vol % CH 4 /N 2 flow, the bands at 966, 1070–1220, and 1465 cm −1 are attributed to the vibration modes of the ν Pd(O2) of the surface peroxo species Pd(O 2 ), [14c, 19] the δ (OO−H) of PdOOH, [14] and the δ (CH) of CH 3 −O−Pd, [15b] respectively. This indicates that C−H bonds are cleaved with the reaction of the active oxygen to form the radical‐like CH 3 species and nearly form the OOH bonds in a transition state.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the strong interaction between the metal and support can modulate the electronic structure of metal catalyst and further improve the catalytic performance. As a catalytic support, BN nanosheet, a structural analog of grapheme, featured with a local polarity B-N bond, has attracted considerable attention due to its excellent acid-base resistance, extraordinary oxidation resistance, and thermal stability (Lin, 2002; Pakdel et al, 2014; Sun et al, 2016; Tran-Thuy et al, 2017). Uosaki et al demonstrated the possibility to functionalize inert Au substrate to become ORR catalysts by BN modified, reducing the overpotential by ca.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 2338 and 2360 cm - represent gaseous CO2 over the Au-CuOx/BN catalyst (Fig. S7) [5], and they are not observed for the Au/BN catalyst. This phenomenon may indicate that the activated oxygen on the Au-CuOx/BN catalyst readily reacts with adsorbed CO.…”
Section: Resultsmentioning
confidence: 99%
“…Supported-Au catalysts have attracted considerable attention and are generally accepted as the most active catalysts for CO oxidation [1,2]. Many factors can affect the activity of supported-Au catalysts, such as Au particle size, the nature of the support [3,4], and the presence of additional promoters [5][6][7]. Notably, varying the support material can significantly influence the catalytic performance of Au in this reaction system as different support materials exhibit different metal-support interactions [8], oxygen activation abilities [9,10], and even surface functional groups [11].…”
Section: Introductionmentioning
confidence: 99%